Safety of influenza vaccination on adverse birth outcomes among pregnant women: A prospective cohort study in Japan. (April 2020) - Ohfuji, Satoko; Deguchi, Masaaki; Tachibana, Daisuke; Koyama, Masayasu; Takagi, Tetsu; Yoshioka, Takayuki; Urae, Akinori; Ito, Kazuya; Kase, Tetsuo; Maeda, Akiko; Kondo, Kyoko; Fukushima, Wakaba; et al.
Highlights: Adverse birth outcomes were reported for 9% of vaccinated pregnant women. The reported proportions were similar between unvaccinated and vaccinated women. Influenza vaccination during pregnancy did not relate to adverse birth outcomes. Abstract: Background: Pregnant women are in the highest priority group for receiving influenza vaccination. However, they may be reluctant to receive the vaccination due to concerns about the influence of vaccination on the fetuses. Methods: This prospective cohort study of 10 330 pregnant women examined the safety of influenza vaccination in terms of adverse birth outcomes. Influenza vaccination during pregnancy was determined from questionnaires before and after the 2013/2014 influenza season. All subjects were followed until the end of their pregnancy. Adverse birth outcomes, including miscarriage, stillbirth, preterm birth, low birth weight, and malformation, were assessed by obstetrician reports. Results: Adverse birth outcomes were reported for 641 (10%) of the 6387 unvaccinated pregnant women and 356 (9%) of the 3943 vaccinated pregnant women. Even after adjusting for potential confounders, vaccination during pregnancy showed no association with the risk of adverse birth outcomes (odds ratio 0.90, 95% confidence interval 0.76–1.07). Vaccination during the first or second trimester displayed no association with adverse birth outcomes, whereas vaccination during the third trimester was associated with a decreased risk of adverse birth outcomes (odds ratio 0.70, 95% confidence interval 0.51–0.98). Conclusions: Influenza vaccination during pregnancy did not increase the risk of adverse birth outcomes, regardless of the trimester in which vaccination was performed, when compared to unvaccinated pregnant women.